Reading by all means - Dubin, Fraida; Olshtain, Elite (USA : Addison-Wesley publishing company, 1981)
Everyone likes a good story. That is why narratives are enjoyable to read. Throughout history, people have told stories, both orally and in writing...
Keywords: English language; English language